2003
DOI: 10.1046/j.1365-4362.2003.01936.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of skin diseases in rural areas of Assiut Governorate, Upper Egypt

Abstract: Infective-parasitic diseases were a major problem particularly among the younger age-group and those of low socio-economic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
84
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 20 publications
12
84
3
1
Order By: Relevance
“…Although such infestations are a common occurrence in our rural population, a study from rural Egypt reports it as the commonest skin condition (27.4%) with pediculosis capitis (19.37%) being the commonest. 10 Studies from India have reported pediculosis capitis more commonly in children (47.1%). 11 We did not record any case of pediculosis in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Although such infestations are a common occurrence in our rural population, a study from rural Egypt reports it as the commonest skin condition (27.4%) with pediculosis capitis (19.37%) being the commonest. 10 Studies from India have reported pediculosis capitis more commonly in children (47.1%). 11 We did not record any case of pediculosis in our study.…”
Section: Discussionmentioning
confidence: 97%
“…This confirms the results of previous studies to the effect that the poorer the household, the greater the odds of frequent head lice infestation among household members, and that the poorest of the poor are the most vulnerable population group. 3,15,16 Therefore, a targeted intervention focusing on extremely poor households or impoverished communities is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…1 Children aged < 12 years show the highest prevalence and bear the highest burden of disease. [2][3][4] Despite the public health relevance of the condition, strategies to effectively control it are not evidence-based, and recurrent head lice infestations are a common problem. 5,6 This is of particular concern in resource-poor communities, where this parasitic skin disease prevails and is associated with considerable morbidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eczema prevalence was also high at 19%. (14) By contrast, the survey carried out in Sumatra, Indonesia(11) showed a lower prevalence of skin problems. In children and adolescents, 28.2% of the population studied had skin disease although, as is usually found, fungal and bacterial infections were the most common diseases seen.…”
Section: The Background To Community Dermatologymentioning
confidence: 95%